2015
DOI: 10.1089/cap.2014.0003
|View full text |Cite
|
Sign up to set email alerts
|

Loxapine Add-on for Adolescents and Adults with Autism Spectrum Disorders and Irritability

Abstract: Objectives: Our clinical experience with low dose loxapine (5-15 mg/day) suggests promising efficacy and safety for irritability in autism spectrum disorders (ASD). We studied low dose loxapine prospectively in adolescents and adults with ASD and irritability. Additionally, we measured loxapine and metabolite concentrations, and brain-derived neurotrophic factor (BDNF) as a biomarker of neuromodulation. Methods: We performed a 12 week open trial of add-on loxapine in subjects, ages 13-65 years, diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Both showed effectiveness in ameliorating behavioral problems 78,79 . Another drug loxapine, a typical anti-psychotic, was effectiveness as an add-on therapy for irritability in ASD 80 . Ribavirin is another interesting 15 candidate.…”
Section: Autistic Spectrum Disordersmentioning
confidence: 99%
“…Both showed effectiveness in ameliorating behavioral problems 78,79 . Another drug loxapine, a typical anti-psychotic, was effectiveness as an add-on therapy for irritability in ASD 80 . Ribavirin is another interesting 15 candidate.…”
Section: Autistic Spectrum Disordersmentioning
confidence: 99%
“…An open-label 12-week study 147 studied add-on loxapine (BDNF stimulator) doses of 5–15 mg in 16 participants with ASD who were on one or more psychotropics of different types. Most improved in their Clinical Global Impression-Improvement scale (CGI-I) scores and their Aberrant Behavior Checklist- irritability (ABC-I) subscale scores with minimal side effects.…”
Section: Future Directionsmentioning
confidence: 99%
“…First generation antipsychotics (FGAs), also called typical antipsychotics, primarily haloperidol, may still be used occasionally, but most studies have used second generation antipsychotics (SGAs), also called atypical antipsychotics because of a lessened chance of extrapyramidal side effects, dystonic reactions, withdrawal dyskinesia, and tardive dyskinesia (Posey, Stigler, Erickson, & Mc-Dougle, 2008). More recently, an FGA, loxapine, that to some degree resembles an SGA, has found new favor (Hellings, Jadhav, Jain, Jadhov, & Genovese, 2015;Hellings, Reed et al, 2015;Jain, Andridge, & Hellings, 2016). SGAs block postsynaptic serotonin receptors that may provide relative protection against extrapyramidal symptoms (Glick, Murray, Vasudevan, Marder, & Hu, 2001).…”
Section: Types Of Antipsychotics Used In Asdmentioning
confidence: 99%
“…Extrapyramidal side effects were found, but again no significant weight change (Hellings, Jadhav et al, 2015). These investigators then used loxapine as an add-on in adolescents and adults with ASD, with doses of 5 to 15 mg/day in a 12-week study: they found that a number of other psychotropics could be tapered, that there was high efficacy, and that BMI scores actually decreased (Hellings, Reed et al, 2015). Given the favorable metabolic profile, the authors then reviewed 15 charts of adults with ASD who had antipsychotic drug-related weight gain and had loxapine added to their regime.…”
Section: Loxapinementioning
confidence: 99%